ANALYSIS OF GOOD GOVERNANCE IN E-KTP SERVICES AT THE POPULATION AND CIVIL REGISTRATION SERVICE OF NGAWI REGENCY IN 2025: Analisis Good Governance Dalam Pelayanan E-Ktp Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ngawi Tahun 2025 - Budiono; Agus Wiyaka; Harianto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Population administration is a form of public service that plays a crucial role in ensuring the certainty of citizens' legal identity and supporting orderly population administration. The success of the Electronic Identity Card (E-KTP) service is greatly influenced by the implementation of good governance principles, including transparency, accountability, participation, and fairness. This study aims to determine the implementation of the grants policy in the religious sector in Madiun Regency. The type of research that the writer uses is descriptive quantitative research. The population in this study were (1) the employees of the Welfare Section of the Regional Secretariat of Madiun Regency were 6 people; and (2) Management of Community Organizations (Takmir Masjid and Mushola, etc.) recipients of 79 grants from the Madiun Regency Government. So that the population in this study was 85 people. The data collection techniques used questionnaires, documentation and interviews. While the data analysis in this study used a qualitative descriptive analysis. This study concludes that the application of good governance principles positively contributes to improving the quality of e-KTP services and supports the realization of orderly population administration. Therefore, strengthening public digital literacy, increasing the capacity of service personnel, optimizing the use of information technology, and strengthening oversight mechanisms and public participation are necessary to sustainably improve the quality of population administration services.